2018
DOI: 10.1186/s12911-018-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging healthcare utilization to explore outcomes from musculoskeletal disorders: methodology for defining relevant variables from a health services data repository

Abstract: BackgroundLarge healthcare databases, with their ability to collect many variables from daily medical practice, greatly enable health services research. These longitudinal databases provide large cohorts and longitudinal time frames, allowing for highly pragmatic assessment of healthcare delivery. The purpose of this paper is to discuss the methodology related to the use of the United States Military Health System Data Repository (MDR) for longitudinal assessment of musculoskeletal clinical outcomes, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 58 publications
(62 reference statements)
1
49
0
Order By: Relevance
“…1 ). Additional details of the extraction for cohort have been published and available (Rhon et al 2018 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Additional details of the extraction for cohort have been published and available (Rhon et al 2018 ).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review identified nine predictive models for determining opioid abuse, and the majority were based on diagnosis codes (ICD-9) (Alzeer et al 2018 ). Specific details for how these variables were extracted and their relevance to prognosis in individuals with musculoskeletal outcomes have been published (Rhon et al 2018 ). Seventeen variables were identified as potential predictors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These comorbid conditions were chosen because they have an established relationship with opioid use, and they have been shown to impact the prognosis of musculoskeletal disorders. 34 The specific International ICD codes used to identify these comorbidities are listed in the Supplemental Appendix . Based on guidelines used by the Armed Forces Health Surveillance Branch (central epidemiologic resource for the U.S. Armed Forces), 35 at least 2 separate visits for each comorbidity needed to be present for it to be counted.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying the onset of OA after traumatic injury is challenging because surveillance is needed in systems that can track comprehensive health services utilization for patients over long periods. The Military Health System (MHS) is one of very few large closed systems that exist in the United States, with very little missing data (Rhon, Clewley, Young, Sissel, & Cook, ).…”
Section: Introductionmentioning
confidence: 99%